2011
DOI: 10.1038/npp.2011.303
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT2C Receptor Agonist Lorcaserin Reduces Nicotine Self-Administration, Discrimination, and Reinstatement: Relationship to Feeding Behavior and Impulse Control

Abstract: Lorcaserin ((1R)-8-chloro-1-methyl-2,3,4,5-tetrahydro-1H-3-benzazepine HCl) is a selective 5-HT 2C receptor agonist with clinical efficacy in phase-III obesity trials. Based on evidence that this drug class also affects behaviors motivated by drug reinforcement, we compared the effect of lorcaserin on behavior maintained by food and nicotine reinforcement, as well as the stimulant and discriminative stimulus properties of nicotine in the rat. Acutely administered lorcaserin (0.3-3 mg/kg, subcutaneous (SC)) dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
127
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(145 citation statements)
references
References 78 publications
(95 reference statements)
17
127
1
Order By: Relevance
“…Drugs that activate 5-HT 2C receptors hold promise for the treatment of psychoses and psychostimulant abuse, in part because of their ability to modulate central dopamine signaling and their effectiveness in preclinical models and at least one clinical study (Di Matteo et al, 2004;Shen et al, 2010;Higgins et al, 2012;Cunningham et al, 2013). Herein is described (2)-MBP, a novel and potent 5-HT 2C receptorspecific agonist with 5-HT 2A and 5-HT 2B competitive antagonist and inverse agonist properties that is effective in preclinical mouse models of psychoses, does not affect locomotion on its own, and reduces palatable food intake, important properties distinguishing it from available antipsychotic drugs that suppress locomotion and increase appetite, leading to obesity (Stip et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Drugs that activate 5-HT 2C receptors hold promise for the treatment of psychoses and psychostimulant abuse, in part because of their ability to modulate central dopamine signaling and their effectiveness in preclinical models and at least one clinical study (Di Matteo et al, 2004;Shen et al, 2010;Higgins et al, 2012;Cunningham et al, 2013). Herein is described (2)-MBP, a novel and potent 5-HT 2C receptorspecific agonist with 5-HT 2A and 5-HT 2B competitive antagonist and inverse agonist properties that is effective in preclinical mouse models of psychoses, does not affect locomotion on its own, and reduces palatable food intake, important properties distinguishing it from available antipsychotic drugs that suppress locomotion and increase appetite, leading to obesity (Stip et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence exists that 5-HT2C agonists do not only inhibit food intake, e.g. the consummatory component of feeding behaviour, but also the preceding appetitive phase, which is not yet food related [82,359]. Combining the 5-HT2C/1B agonist mCPP with the CB1 antagonist/partial agonist rimonabant synergistically reduced motivated feeding behaviour in an operant paradigm in mice [360].…”
Section: Serotonin and The Pharmacotherapy Of Obesitymentioning
confidence: 99%
“…In clinical studies, lorcaserin is well tolerated and decreases food intake and body weight (Smith et al, 2009(Smith et al, , 2010Chan et al, 2013;Aronne et al, 2014) at doses that have low potential for producing heart valve disease (Weissman et al, 2013) or abuse (Shram et al, 2011), effects commonly associated with 5-HT 2B and 5-HT 2A receptor agonists, respectively (Nichols, 2004;Hutcheson et al, 2011). In addition to preclinical studies demonstrating that lorcaserin decreases food intake and body weight (Smith et al, 2008;Thomsen et al, 2008;Higgins et al, 2013b;Grottick et al, 2015), lorcaserin is also shown to decrease nicotine selfadministration and the reinstatement of responding for nicotine in rats (Levin et al, 2011;Higgins et al, 2012Higgins et al, , 2013b.…”
Section: Introductionmentioning
confidence: 99%